Family history of cancer other than breast or ovarian cancer in first-degree relatives is associated with poor breast cancer prognosis. (April 2017) - Song, Jun-Long; Chen, Chuang; Yuan, Jing-Ping; Li, Juan-Juan; Sun, Sheng-Rong
Abstract: Objective: Whether a first-degree family history of others cancers (FHOC) than breast or ovarian cancer (BOC) is associated with breast cancer prognosis remains unknown. Thus, the aim of the present study was to clarify this issue. Methods: Women who were diagnosed with invasive breast cancer at the Renmin Hospital of Wuhan University from 2010 to 2013 were included in the study. The demographic and clinicopathological characteristics of these patients were extracted. FHOC was considered positive for any patient who had a relative who had been diagnosed with cancer other than BOC. Disease-free survival (DFS) was calculated based on the date of diagnosis. DFS was analyzed using the Cox proportional hazards model. Results: A total of 434 breast cancer patients were included in this study. Among these patients, 61 (14.06%) had a positive FHOC in first-degree relatives. Patients with a positive FHOC tended to have HER2-positive breast cancer ( p  = 0.03). In the survival analysis, FHOC was associated with poor DFS in both univariate (HR = 2.21 (1.28–3.83), 95% CI: 1.28–3.83, p  < 0.01) and multivariate (HR = 2.50, 95% CI: 1.24–5.04, p  = 0.01) analyses, especially in patients with luminal A subtypes. Conclusion: The results demonstrated an increased risk of recurrence in breast cancer patients with FHOC, especially in patients with luminal A subtype. Highlights: Many breast cancer patients have family history of cancer. Patients with family history of other cancer than breast cancer or ovarian cancer (FHOC) tend to has HER2 positive cancer. Patients with FHOC has poorer disease-free survival.